Outcomes and costs of treating hepatitis C patients with second-generation direct-acting antivirals: results from the German Hepatitis C-Registry - Krüger, Kathrin; Pathil-Warth, Anita (European journal of gastroenterology & hepatology, 2019)
ObjectiveChronic hepatitis C virus infection is associated with a significant health burden. Long-term consequences are the development of liver cirrhosis and hepatocellular carcinoma. The introduction of direct-acting antivirals (DAA) has led to an increase in sustained virologic response rates (SV